DINAMIKA EMOSI TOKOH UTAMA DALAM NOVEL SEPORSI MIE AYAM SEBELUM MATI KARYA BRIAN KHRISNA - Medikana, Rosaria; Maizar Karim; Dwi Rahariyoso (STKIP Subang, 2026)
This study aims to describe the emotional dynamics of the main character, Ale, in the novel Seporsi Mie Ayam Sebelum Mati by Brian Khrisna using David Krech’s theory of emotions. The focus of the study is to identify the forms of emotions experienced by the character based on the categories of guilt, repressed guilt, self-punishment, shame, sadness, hatred, and love. This research employs a literary psychology approach with a qualitative descriptive method. The data consist of narrative excerpts and dialogues that reflect the emotional expressions of the main character. The data were collected through close reading and note-taking techniques and then analyzed based on emotional indicators proposed by Krech. The findings reveal that Ale’s emotional dynamics are predominantly characterized by self-punishment, shame, and sadness. These emotions emerge as a result of bullying, social rejection, and unfair treatment he has experienced since childhood through adulthood. Meanwhile, guilt, repressed guilt, hatred, and love are not portrayed significantly. The study concludes that prolonged social rejection shapes destructive emotional patterns that influence the main character’s self-concept and psychological condition.